Ethnomathematics: Integrating a Perspective and Alternative to Build Numeracy Mindset - Maharbid, Dian Anggraeni; Farhana, Husna; Widiasyahr, Apriyanti (International Conference on Elementary Education, 2025)
The persistent challenges in mathematics education, particularly low mathematical literacy and declining student motivation, necessitate innovative pedagogical approaches. This study exploresethnomathematics as an integrative perspective and alternative strategy to build a numeracy growth mindset among elementary students. Ethnomathematics, which recognizes the cultural dimensions of mathematical practices, offers contextual learning experiences that bridge abstract mathematical concepts with students' daily lives. This research examines how integrating ethnomathematics principles within Indonesia's Merdeka Curriculum can enhance numeracy competencies while fostering positive mathematical dispositions. Through analysis of traditional Indonesian cultural practices—including batik patterns, traditional architecture, games, and rituals—this study demonstrates how culturally-relevantmathematical contexts can transform learning environments and develop growth mindsets in numeracy. The findings suggest that ethnomathematics-based approaches address multiple challengessimultaneously: improving conceptual understanding through meaningful connections, increasing motivation through cultural relevance, and creating inclusive learning environments that support diverselearners. This research contributes to the growing body of evidence supporting culturally responsive mathematics education as a viable solution to numeracy problems in Indonesian education.